ADCP current measurements (75 kHz) during RV MARIA S. MERIAN cruise MSM121 - Ilmar Leimann; Christian Mertens (PANGAEA, 2025)
Upper-ocean current velocities were measured along the track of the cruise MSM121 (22 September — 16 October 2023) using a vessel-mounted acoustic current Doppler profiler (ADCP). The instrument was a Teledyne RD Instruments 75-kHz Ocean Surveyor, with the transducer was installed 6.0 m below the waterline. The instrument was operated in narrowband mode to achieve the maximum possible range. Velocity data were recorded in 100 8-m bins. The navigational data, as well as heading, pitch and roll data, were recorded together with the velocity measurements by the data acquisition software (VmDAS). The velocity data were converted into earth coordinates and averaged into one-minute intervals. A water track calibration was used (OSADCP_Toolbox) to determine misalignment angle (0.678°) and amplitude factor (1.010). The accuracy of the velocity data varies, and depends on the number of available good pings in each depth cell during one measurements interval.